Environmental Ethics in Community-Based Waste Management: A Case Study of the Al-Huda Waste Bank in Rancah - Pryanka, Nallagyta; Suhendi (Asosiasi Ahli Administrasi Indonesia, 2025)
This study investigates the application of environmental ethics in the community-based waste management system implemented at the Al-Huda Central Waste Bank in Rancah District, Ciamis Regency. The research aims to identify how ethical principles shape the attitudes, behaviors, and participation patterns of community members involved in waste management activities. Using a descriptive qualitative method, data were collected through observations, in-depth interviews, and document analysis involving waste bank managers, volunteers, and local residents. The findings show that fundamental ethical values including responsibility, care, honesty, moderation, and sustainability are consistently integrated into the daily operations of the waste bank and inform the decision-making processes of its participants. These values are reflected in educational programs, waste-saving schemes, sorting practices, and recycling initiatives that encourage environmentally conscious habits and strengthen collective awareness. The study also reveals that the waste bank not only provides economic benefits for the community but also fosters social cohesion, mutual cooperation, and a shared sense of stewardship toward the local environment. Overall, the research demonstrates that environmental ethics function as both moral guidance and practical frameworks that enhance the effectiveness, relevance, and long-term viability of community-based waste management systems, offering valuable insights for the development of sustainable environmental governance at the grassroots level.